KETIDAK TELITIAN PENELITIAN - Abdullah, Abdullah (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2006)
This paper had been written to respons on Taslim Lukman research based on his papaer as presentedin Wacana. I am very sad to say that the result of the research is very bad based on statistical considerations.